DEVELOPMENT OF INTERACTIVE ONLINE-BASED TEACHING MATERIALS FOR PHYSICS SUBJECTS IN CLASS X VOCATIONAL SCHOOLS - Yusdarina Yusdarina; Irma Sakti (Pendidikan Fisika UIN Alauddin Makassar, 2021)
This study aims to develop learning products in the form of interactive online-based teaching materials for class X students of physics subject measurement materials at SMK Muhammadiyah Bungoro. This type of research is development research. The model used in this development is carried out in 5 stages, namely: analysis (analyze), design (design), development (development), implementation (implementation), and evaluation (evaluation). The results achieved in this study are a product in the form of interactive online-based teaching materials that are applied in learning Physics at SMK Class X. The results of the validation assessment of material experts and media experts are in the very valid category with an average value of 89.22 and 84.17. The results of the analysis of subject teacher responses and student responses are in the very practical category with an average value of 95.0 and . 84.48. The results of the evaluation of students showed classical completeness with an average value of 83.60. This shows that interactive online-based teaching materials are suitable for use in online learning for class X physics subjects.